The effects of dietary eggshell with membrane and olive leaf extract supplementation on performance, carcass characteristics and some biochemical parameters of quails exposed to heat stress - Erisir, Zeki; Ozcelik, Mehtap; Azman, Mehmet Ali; Iflazoglu Mutlu, Seda; Simsek, Ulku Gulcihan; Baykalir, Yasin; Ciftci, Mehmet (Ankara Univ Press, 2020)
This study was conducted to investigate the effects of eggshells with membrane (ESM), the eggshells with membrane that had absorbed olive leaf extract (ESM+OLE) and olive leaf extract (OLE) additives on the performance, immunity, and oxidant-antioxidant metabolism of Japanese quails exposed to heat stress. In the experiment, a total of 128 fifteen-day-old quails were divided into 4 groups with 4 replicates. The control group was fed with a maize-soybean based basal diet; the ESM group was fed with a basal diet supplemented with 2% ESM; the ESM+OLE group was fed with a basal diet consisting of 2% ESM and 200 ppm olive leaf extract and the OLE group was fed with a basal diet supplemented with 200 ppm olive leaf extract. At the end of the study, carcass characteristics and blood parameters were determined. The highest daily body weight gain and the lowest feed conversion ratio were observed in the OLE group (P<0.05). OLE was added into feed, MDA levels in the liver and heart decreased significantly (P<0.001), whereas, GSH-Px and SOD activities in both tissues alongside the GSH levels in the heart increased significantly (P<0.001). The ESM was found to significantly reduce liver MDA levels (P<0.001), and increase GSH-Px activity in both tissues, along with SOD activity and GSH levels in the heart (P<0.001). Consequently, the addition of ESM and OLE to the diets positively affected daily body weight gain, serum triglyceride, liver, and heart tissue MDA levels in the quails exposed to heat stress.
Sıcaklık stresi altındaki bıldırcınlarda yeme zarlı yumurta kabuğu ve zeytin yaprağı özütü ilavesinin performans, karkas özellikleri ve bazı biyokimyasal parametreler üzerine etkisi
Keywords: Biochemical parameters; eggshell with membrane; olive leaf extract; performance; quail